The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0084231
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Third Binding Site of Arsenic in Human Arsenic (III) Methyltransferase

Abstract: Arsenic (III) methyltransferase (AS3MT) catalyzes the process of arsenic methylation. Each arsenite (iAs3+) binds to three cysteine residues, methylarsenite (MMA3+) binds to two, and dimethylarsenite (DMA3+) binds to one. However, only two As-binding sites (Cys156 and Cys206) have been confirmed on human AS3MT (hAS3MT). The third As-binding site is still undefined. Residue Cys72 in Cyanidioschyzon merolae arsenite S-adenosylmethyltransferase (CmArsM) may be the third As-binding site. The corresponding residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…DMA loaded negatively (−100) on PC1 (eigenvalue = 2.08), and MMA (67) and iAs (80) both loaded positively. For PC2 (eigenvalue = 0.93), MMA loaded positively (75), iAs loaded negatively (−60), and DMA had a loading near zero (2). We multiplied PC1 by −1 so that higher PCs scores represent more methylation (i.e, more DMA% and MMA% respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DMA loaded negatively (−100) on PC1 (eigenvalue = 2.08), and MMA (67) and iAs (80) both loaded positively. For PC2 (eigenvalue = 0.93), MMA loaded positively (75), iAs loaded negatively (−60), and DMA had a loading near zero (2). We multiplied PC1 by −1 so that higher PCs scores represent more methylation (i.e, more DMA% and MMA% respectively).…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanism(s) by which these SNPs influence metabolism remain unclear. Kinetic studies have shown that the AS3MT binding affinity differs for the first methylation step as compared to the second step (73,74) and there are differences in the number of binding sites required for each of the methylation steps (75). These differences in AS3MT kinetics for the first vs. the second methylation step suggest that it possible that the SNPs in this region could have different effects on these two methylation reactions this population.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al and our group have analyzed the functions of these crucial Cys residues and have confirmed that Cys61, Cys156, and Cys206 are the active sites of hAS3MT [26] [30] . Like Cys72 in CmArsM, Cys61 moves toward Cys156 and Cys206 upon AdoMet binding, and leaves away after the first step methylation [30] . However, it is not clear if a disulfide bond is formed between the active residues of during the catalytic cycle.…”
Section: Introductionmentioning
confidence: 68%
“…Previous studies have suggested that Cys72 may be important for the maintenance of hAS3MT conformation [29] , and Cys61 may be the third binding site for iAs 3+ [30] . However, we did not detect the peptides corresponding to Cys61 (IA-modified) and Cys72 (IA-modified) in hAS3MT or its reduced form.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation